Bird strike substantiation of a rotor component by simulation - Test correlation, residual strength capability - Laillet, E.; Vagnot, A.; Richer, L.; Halbout, S. (My University, 2014)
Bird strike strength capability is required by the regulation for large rotorcrafts [1]. For rotor components, substantiations were up to now only performed on components exposed to bird strikes (by the trajectory of the bird through the aircraft), and whose strength could lead to a catastrophic situation (“candidates” were only non massive components). In practical terms, the components generally substantiated were only the main and tail pitch control rods under direct strike. The compliance was classically shown by analytical calculations based on bird strike test of similar design and test conditions. Thanks to the improvements of simulation capabilities in bird trajectories and FE analysis, it is now possible to have a more accurate evaluation of the components to be impacted, as well as improved FE softwares and solvers, for test correlations / simulations and residual strength capabilities evaluation. This paper describes the process developed for substantiating by FE analysis a main rotor pitch control rod subjected to a bird strike, up to the safe landing of the aircraft. Then, the substantiation methodology is applied to a new design of pitch rod. It provides details on the flight conditions to be considered at the time of the impact, elasto-plastic behaviour law of the pitch rod material, simulation conditions, hypothesis and results of the bird strike itself by comparison to a test performed on the same component in the same conditions (see Figure 2). Once the bird strike test is correlated by FE simulation of the pitch rod tested, this process is applied on the other design of pitch rod. Then, a FEM analysis is realized in order to determine the residual static and fatigue strength of the component (the strength or stability could be affected by a permanent deformation).